2018
DOI: 10.1111/codi.14095
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome and quality of life in patients with total colonic aganglionosis in the Netherlands

Abstract: Children and adolescents with TCA report lower health-related QoL compared with healthy peers, especially in the physical domain. We suggest standardized follow-up and prospective longitudinal future research on functionality and QoL of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…Less often 0 (0) 0 (0) 0 (0) 0 (0) 0 (0) Always/daily 1 (2) 1 (5) 0 (0) 0 (0) 0 (0) Values in parentheses are percentages unless indicated otherwise; *values are median (range). SIAA, straight ileoanal anastomosis; JIAA, J pouch-ileoanal anastomosis; BFS, bowel function score (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). †P = 0⋅007 versus SIAA and Duhamel procedure (Kruskal-Wallis test); all other comparisons were not significant.…”
Section: Frequency Of Bowel Movementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Less often 0 (0) 0 (0) 0 (0) 0 (0) 0 (0) Always/daily 1 (2) 1 (5) 0 (0) 0 (0) 0 (0) Values in parentheses are percentages unless indicated otherwise; *values are median (range). SIAA, straight ileoanal anastomosis; JIAA, J pouch-ileoanal anastomosis; BFS, bowel function score (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). †P = 0⋅007 versus SIAA and Duhamel procedure (Kruskal-Wallis test); all other comparisons were not significant.…”
Section: Frequency Of Bowel Movementsmentioning
confidence: 99%
“…All definitive surgical procedures in TCA aim to achieve faecal continence by preserving the sphincter musculature, even though the internal anal sphincter remains aganglionic and is a potential cause of obstructive defaecation and HAEC 13,14 . In the long-term, nutritional status and growth may be concerns, owing to loss of intestinal length, dysmotility and malabsorption 1,[15][16][17] . To date, no reconstructive surgical technique has emerged as superior to others with regard to functional outcomes or complications 3,4,18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…To assess HrQoL in children with BA, we used the internationally validated CHQ. 12,13 This questionnaire has been developed to test both physical and psychosocial HrQoL of children aged 5 years and older. 14 The CHQ consists of a 50item parent-proxy form (CHQ-PF50), and an 87-item childreported form (CHQ-CF87) for children aged 10 years or older.…”
Section: Measurementsmentioning
confidence: 99%
“…Long-term followup studies have shown that hypermotility problems persist even when the pull through is done after the child is toilet trained, most frequently presenting involuntary loss of stool during the night, abdominal pain, and a poor quality of life due to daily life limitations. 20 An example of the importance of these symptoms is revealed in one study which showed that the most common questions posted on the Hirschsprung's disease Facebook page are regarding the management of severe diaper rash, followed closely by questions regarding bowel management, long-term outcomes, potty training, and dietary issues. 21 We also emphasize the low growth curve in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age at pull through was 17.5 months (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). At the time of the ileoanal pull through, eight of nine of these patients were not toilet trained for urine.…”
Section: Patients Who Underwent a Primary Pull Through At Our Center mentioning
confidence: 99%